PENGARUH GROUND GRANULATED BLAST FURNACE SLAG SEBAGAI PENGGANTI SEBAGIAN SEMEN PADA PAPAN SERAT RINGAN - Ananda Chaerul Imam; Anni Susilowati; Pratikto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
ABSTRACT Lightweight fiberboard is a composite material consisting of a Ground Granulated Blast Furnace Slagwaste mixture, foaming liquid, cement, sand, and water. It is necessary to optimize the use of environmentally friendly materials such as Ground Granulated Blast Furnace Slagwaste which has a specification of the main content, namely calcium, aluminum and silica which have a chemical composition not different from the minerals in portland cement. Materials for foam mortar are currently being developed and can be an option for fiberboard mixtures that have a light weight. Behind the advantages of foam cement board which has a light weight and the use of glass fiber on lightweight fiberboard can increase the flexural strength. The research was conducted to obtain the flexural strength of lightweight fiberboard based on SNI 001-0449-2006 and SNI 15-0233-1989 regarding Quality and Test Method of lightweight fiberboard. Variation used 1 PC : 0% GGBFS : 1,2 Sand : 13% Glass Fiber, 0,8 PC : 20% GGBFS : 1,2 Sand : 13% Glass Fiber, 0,6 PC : 40% GGBFS :1,2 Sand : 13% Glass Fiber, 0,4 PC : 60% GGBFS :1,2 ??Sand : 13% Glass Fiber, 0,2 PC : 80% GGBFS :1,2 ??Sand : 13% Glass Fiber with FAS 0,15. The results of the analysis show that the more waste is used, the lower the density value, the specific gravity value, and the water absorption value. Increase the value of thickness expansion, moisture content value, nailing ability, and has an optimum value of flexural strength at a variation of 20% ground granulated blast furnace slag waste by 90 kg/cm² According to the requirements of SNI 15-449-2006 that all lightweight fiberboard test specimens for flexural strength testing are included in PSKT (High Density Fiberboard). Keywords: Foam mortar; GGBFS; Glass fiber; Lightweight fiberboard.